CONSOLIDATION OF DEMOCRATIC INSTITUTIONS – THE CASE OF SERBIA - Golubović, Nataša L; Džunić, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Due to the violation of the elements that guarantee the respect of democratic norms and institutions in the last few years, Serbia is most often characterized as a deficient democracy, and has recently been classified as a hybrid regime. From the beginning of the transition, in the implementation of political and economic reforms in Serbia periods of modest progress in the field of political and economic transformation alternate with periods of stagnation, and even setbacks in important segments of reforms. Indicators of political and economic reforms point to the strengthening of extractive institutions. Extractive institutions protect the economic and political interests of privileged groups to the detriment of the rest of society. This leaves fewer resources available to stimulate economic growth and job creation. This has a reciprocal negative impact on the legitimacy of the political regime and trust, which are necessary for the implementation of economic reforms. Serbia's failure to provide stronger economic growth is largely due to extractive institutions that determine the business environment. The absence of a more even distribution of political power, weaknesses in the mechanisms of cheks and balances, deficiencies in the sphere of the rule of law, widespread corruption, problems in the sphere of protection of property rights, indicate the development of extractive institutions in Serbia. What is happening in Serbia during the transition period can be seen as a historical heritage that adapts to the current social environment and has a great impact on institutional performance and democratic consolidation. Prolonged exposure to extractive institutions creates a cumulative effect of institutional learning in Serbia, where individuals become vulnerable to political abuse, dependent on the state and unwilling to use political means to make government accountable to society, contributing to a vicious circle of extractive political and economic institutions. Identifying the mechanisms of such accumulation, which include prolonged exposure to extractive institutions, as well as the transmission of cultural patterns from older generations who have long experience with extractive institutions, is a complex research task.
Keywords: extractive institutions; democratic consolidation; institutional efficiency; rule of law; corruption